TIKTOK PLATFORM AS AN ENGLISH LEARNING TOOL: ELEVATING STUDENTS’ SPEAKING SKILL - Suryani, Maylina Dwi; Anggreni, Afrillia; Marhum, Mochtar; Mashuri, Mashuri (TELL - US JOURNAL, 2025)
AbstractTikTok platform has been one of innovative social media in bridging English Language Teaching (ELT). Thus, this study aims to prove whether the use of the TikTok platform, especially the duet and vlog video features can improve the speaking skills of tenth-grade students of SMA Negeri 1 Moutong. Three components of speaking skills, namely fluency, accuracy, and comprehensibility were the focus of this study. A pre-experimental design with a one-group pre-test and post-test design was utilized. The sampling technique used was purposive sampling, with a sample size of 31 students. The data were collected through speaking tests in terms of pre-test and post-test. The analysis results point out that the mean pre-test score of the students was 40, while the mean post-test score increased to 64. The statistical test used a t-test with degrees of freedom (df) = n – 1 = 31 – 1 = 30, resulting in a t-counted value of 16,30, while the t-table value at the 0.05 significance level was 2,042. Thus, the t-counted value is higher than the t-table value, so the research hypothesis is accepted. This proves that the use of the TikTok platform can improve students' speaking skills, particularly in terms of fluency, accuracy, and comprehensibility. These findings suggest that teachers can use TikTok as an effective alternative tool in English-speaking learning to improve students' motivation, creativity, and participation in class.Keywords: Accuracy, Comprehensibility, Fluency, Speaking, TikTok platform